2020
DOI: 10.2185/jrm.2019-016
|View full text |Cite
|
Sign up to set email alerts
|

Surgical symptomatic knowledge among medical staff and community health workers in rural Cambodia: a descriptive study for workforce improvement

Abstract: Objective: The surgical workforce needs to at least double by 2030. To increase the workforce, training for non-physician healthcare professionals and community health workers (CHWs) in rural areas is promising to decrease the numbers of untreated surgical patients. Nevertheless, few studies have been conducted on surgical activities of non-physician healthcare professionals and CHWs in rural Cambodia. We sought to measure the level of knowledge of surgical symptoms, and identify factors associated with it. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Furthermore, a previous study indicated that organochlorines greatly influenced the health of pregnant women, especially in low-income groups 14 ) . Thus, Cambodia is a suitable area for surveying the health effects associated with pesticide poisoning among farmworkers and identifying groups highly affected by these problems 15 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a previous study indicated that organochlorines greatly influenced the health of pregnant women, especially in low-income groups 14 ) . Thus, Cambodia is a suitable area for surveying the health effects associated with pesticide poisoning among farmworkers and identifying groups highly affected by these problems 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was to identify the characteristics of several pesticide poisoning symptoms and to identify protective habits that effectively prevented these symptoms among farmworkers in Kratie, where such poisoning is an urgent public health problem 15 ) .…”
Section: Introductionmentioning
confidence: 99%